O programa segundo tempo em Goiânia e a política pública de esporte e lazer no Brasil a partir da criação do Ministério do esporte. - OLIVEIRA, Marcos Flávio Mércio de (2010)
The study of public policy for sport and leisure from the creation of the Sports Ministry in 2003 is the focus of this work. The aim was to understand how the sport was treated as a social right, can contribute to the reduction or reversal of inequalities in a peripheral society like Brazil. Therefore, it was chosen as study object the Half-Time Program, under the responsibility of the National Department of Sport Education, the Ministry of Sports. By approaching the sport from different perspectives of the sociology of sport, we discuss the connections between the modern state with the sport and what the concepts and major difficulties for the development of Half-Time Program in general and more specifically in the city of Goiania. In the field of social policy discusses the relationship centralization / decentralization of political sport.